Does dividend matter on stock performance during resilient time - Stephanus R. Waworuntu; Sebastian Andrew Waworuntu (President University, 2022)
This research aims to analyze dividend contribution to the stock price performance in the Indonesia Stock Exchange during the resilient time of the Covid19 pandemic. The analysis uses selected firm-specific explanatory variables of Dividend per share (DPS), Dividend yield (DY), Dividend payout ratio (DPR), Book value per share (BV), Earnings per share (EPS), Price-earnings ratio (PER), and firm size in terms of market capitalization (FS). Data is taken from the IDX Index of Dividend-20, which measures the performance of the share price consisting of 20 stocks that have distributed cash dividends for the last three years. The data used during these challenging periods was taken from the year 2018 (before the Covid19 pandemic), the year 2019 (the early period of Covid19), the year 2020 (the pandemic period), and the year 2021 (the vaccination period as an early sign of exiting the pandemic). Data is processed on a computer by applying multivariate analysis using multiple regression analysis with the stepwise method to obtain which model has a relationship toward share price performance and those excluded from the model. This study has concluded that Book value per share (BV) and Earnings per share (EPS) have a significant relationship with the price performance in the observed periods. In contrast, Dividend yield (DY) moves in the opposite direction. These findings have shown that dividends are not significantly contributed to the stock performance during the resilient time, while companies that could maintain better profitability and equity will be better off during the observed periods.